Fabrication and characterization of glycogen-based elastic, self-healable, and conductive hydrogels as a wearable strain-sensor for flexible e-skin. (1st December 2020) - Hussain, Imtiaz; Ma, Xiaofeng; Luo, Yanlong; Luo, Zhenyang
Abstract: Developing natural polymer-based elastic and self-healable hydrogel materials and devices with functions similar to or beyond those of skin has received considerable attention. Such materials possess an impact on the lifetime and potential applications in various fields, such as wearable strain sensors, prosthesis, soft-robotics, and health monitoring systems. Herein, we report glycogen-based elastic, self-healable, and conductive hydrogel as a strain sensor for soft e-skin, which is comprehended by a physically cross-linked biopolymer-based system and containing iron (III) ions intercalated with poly (acrylic acid). The designed hydrogel successfully fulfills all the above-mentioned competencies; self-healing efficiency greater than 97%, fracture stress at 1.12 MPa, elongation at the break about 1420%, a fracture toughness equal to 10.17 MJm −3, and electrical conductivity of 22 S m −1 . The use of nature-inspired hydrogels, by using a natural polymer as a skeleton may open new ways for the fabrication of intrinsically elastic and self-healable sensors for e-skin applications. Graphical abstract: Image 1 Highlights: An intrinsic self-healing hydrogel is fabricated by a facile and cost-effective method. Biodegradable, biocompatible, hydrophilic, and ecofriendly, the natural polymer was used as a skeleton. The hydrogel exhibits self-healing, robustness, notch insensitivity, and conductive properties. The hydrogels demonstrate a resistivity type strain sensor that recognizes refined physiological signals.